Answer:
three solutions: {-3, -3, 0}
Explanation:
This polynomial has already been factored, and the factors are x, x + 3 and x = +3. To solve this equation, set each of the factors equal to zero separately and solve each of the resulting equations:
x = 0 is a solution; the given equation equals zero when x = 0.
The next factor is x + 3; setting this equal to 0 yields the solution x = -3.
The last factor is x + 3; x = -3 is the third solution.
In summary, (x + 3)(x = 3) = 0 has two solutions; we call them "repeated roots." x(x + 3)(x = 3) = 0 has three solutions: {-3, -3, 0} of which two are "repeated."